Enhanced quantum efficiency of horizontally aligned individual InGaN/GaN nanorod LEDs by self-assembled Ag nanoparticles - Kim, Taehwan; Uthirakumar, Periyayya; Cho, Yeong-Hoon; Nam, Ki Hoon; Lee, In-Hwan (Elsevier BV, 2024)
Integration of metal nanoparticles (NPs) in proximity to the InGaN/GaN-based individual nanorod light-emitting diodes (nano-LEDs) can provide a platform to improve the emission efficiency through localized surface plasmon (LSP) coupling effect. This work evaluates an optimizing process for fabricating self-assembled Ag NPs on the surface of horizontally aligned individual nano-LEDs via thermal evaporation/dewetting techniques. The closely integrated Ag NPs on each nano -LED accelerate a strong LSP energy coupling efficiency of 70 % with a fast decay lifetime of 2.04 ns. The self-assembled Ag NPs/nano-LEDs exhibit nearly 130 % and 290 % enhancement in electroluminescent and cathodoluminescent performance compared with reference nanorod LEDs. Furthermore, numerical simulation is performed to correlate the degree of LSP coupling effect concerning changes in particle size and inter-particle distance between the Ag NPs. Thus, the realization of self-assembled Ag NPs/nano-LEDs can prove the concept of the idea to enhance emission efficiency suitable for next-generation display technology.